Determination of Income Inequality: The Influence of Financial Inclusion, Economic Growth, And Human Capital - Nabilla, Anisa Ayu; Pangestuty, Farah Wulandari (Contemporary Studies in Economic, Finance and Banking, 2026)
This study aims to analyze the factors affecting income inequality (Gini Index), highlighting the roles of Financial Inclusion, Economic Growth (proxied by GRDP per capita), and Human Capital (proxied by the Human Development Index and the Open Unemployment Rate). The analytical method employed is panel data regression using a Fixed Effect Model (FEM). Based on the analysis of quarterly panel data from 6 cities in DKI Jakarta Province for the 2020-2022 period, the research yields the following results. The Financial Inclusion Index and the Human Development Index have a negative and significant effect on income inequality. Conversely, GRDP per capita has a positive and significant effect. However, the Open Unemployment Rate was found to have no significant impact on income inequality. These findings suggest that improvements in financial inclusion, economic growth, and human capital do not automatically guarantee equity in the DKI Jakarta Province. This study contributes to the empirical literature and offers policy recommendations for tackling the issue of income inequality in the DKI Jakarta Province.